Pulsed electric field increases the extraction yield of extra virgin olive oil without loss of its biological properties - Martínez-Beamonte, Roberto; Ripalda, Marina; Herrero-Continente, Tania; Barranquero, Cristina; Dávalos, Alberto; López de las Hazas, María Carmen; Álvarez-Lanzarote, Ignacio; Sánchez-Gimeno, Ana Cristina; Raso, Javier; Arnal, Carmen; Surra, Joaquín C.; Osada, Jesús; et al. (Frontiers in Nutrition, 2022)
Pulsed electric field (PEF) has been used for improving extraction of extra virgin olive oil (EVOO). However, the biological changes induced by the consumption of pulsed electric field-obtained extra virgin olive oil (PEF-EVOO) have not been studied yet. To address these aspects, EVOO oils from Empeltre variety were prepared by standard (STD) cold pressure method involving crushing of the olives, malaxation and decanting and by this procedure including an additional step of PEF treatment, the latter resulted in a 17% increase in the oil yield and minimal changes in chemical composition regarding phytosterols, phenolic compounds and microRNA. Male and female Apoe-deficient mice received diets differing in both EVOOs for 12 weeks, and their plasma, aortas and livers were analyzed. Only in females consuming PEF EVOO, a decreased plasma total cholesterol was observed, without significant changes in atherosclerosis and liver steatosis. Our results showed that the PEF technology applied to EVOO extraction maintains the EVOO quality and improves the oil yield. The equivalent biological effects in atherosclerosis and fatty liver disease of PEF-obtained EVOO further support its safe use as a food